Indian asceticism: power, violence, and play - Carl Olsonl (New Delhi: Oxford University Press, 2015)
"Throughout the history of Indian religions, the ascetic figure is most closely identified with power. A by-product of the ascetic path, power is displayed in the ability to fly, walk on water or through dense objects, read minds, discern the former lives of others, see into the future, harm others, or simply levitate one's body. These tales give rise to questions about how power and violence are related to the phenomenon of play. Indian Asceticism focuses on the powers exhibited by ascetics of India from ancient to modern time. Carl Olson discusses the erotic, the demonic, the comic, and the miraculous forms of play and their connections to power and violence. He focuses on Hinduism, but evidence is also presented from Buddhism and Jainism, suggesting that the subject matter of this book pervades India's major indigenous religious traditions. The book includes a look at the extent to which findings in cognitive science can add to our understanding of these various powers; Olson argues that violence is built into the practice of the ascetic. Indian Asceticism culminates with an attempt to rethink the nature of power in a way that does justice to the literary evidence from Hindu, Buddhist, and Jain sources. "--
"Indian Asceticism attempts explores the interrelated discourses and narratives relating tales of Indian ascetics exhibiting various types of powers. The literary evidence also suggests interconnections between these powers and related phenomena, such as violence, demonic, and language. These types of elements are also intertwined with ludic elements, such as the erotic, comic, and miracles"--
Keywords: Asceticism; Hinduism; Buddhism; Jainism; Hinduism; Religion